Critical Evaluation of the Psychology Curricula of Bachelor’s and Master’s Degrees - Adhikari, Pralhad (Curriculum Development Journal, 2023)
Curricula are the guiding frameworks for the teaching-learning experience in the university. This auto-ethnographic account presents my critical evaluation of the curricula of the bachelor’s and master’s degrees of psychology being used at Tribhuvan University, after 5.5 years of teaching as a permanent faculty. There are some strengths in curricula like a strong theoretical foundation, and significant weightage for practical works, and some weaknesses like lack of integrated approach, ignorance of context, and aimlessness. The strengths can be retained and weaknesses can be corrected to provide psychology education that can meet changing societal or market demands.